Work process of nursing team in alcoholism treatment program - Comper, Emilly; Queiroz Subrinho, Lucas; Batista Portugal, Flávia; Mechelli de Siqueira, Marluce (Guará Journal, 2022)
Alcoholism produces changes in individual and collective heal-th, resulting in very important physical, psychic, and social ma-nifestations,  requiring  a  full  and  networked  intervention.  The  aim of this study is to describe the work process of the nursing team in the Program of Attention to the Alcoholic Patients (PAA) of the University Hospital Cassiano Antônio Moraes (HUCAM) of the Federal University of Espírito Santo (UFES). The technique of general direct observation (professionals) and specific (nursing team) and documentary research (reports, articles, and books) was  used  to  capture  the  reality  of  the  Program’s  assistance.  PAA-HUCAM-UFES is an outpatient service for the treatment of alcoholism  patients,  with  an  interprofessional  approach  com-posed of Nurse, Doctor and Social Worker. The health professio-nals  attend  in  program  on  Mondays,  Wednesdays,  and  Thurs-days. The nursing team develops the Nursing Consultation (CE) with health education activities to supply the Basic Human Ne-eds (NHB) and to promote the self-care of the alcoholic patient, based on Wanda Horta and Orem Theory. Through more than 30 years of experience, the nursing team has been developing the  care  of  the  alcoholic,  seeking  their  autonomy,  their  active  role and respect for their human rights.
Keywords: Self-care; Alcoholism; Nursing